2011
DOI: 10.2174/156720511795563700
|View full text |Cite
|
Sign up to set email alerts
|

FTD and ALS: A Tale of Two Diseases

Abstract: The first reports of disorders that in terms of cognitive and behavioral symptoms resemble frontotemporal dementia (FTD) and in terms of motor symptoms resemble amyotrophic lateral sclerosis (ALS) bring us back to the second half of the 1800s. Over the last 150 years, and especially in the last two decades, there has been growing evidence that FTD signs can be seen in patients primarily diagnosed with ALS, implying clinical overlap among these two disorders. In the last decade pathological investigations and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
175
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(177 citation statements)
references
References 261 publications
1
175
0
1
Order By: Relevance
“…Among the most common are age-related neurodegenerative disorders, such as Alzheimer's disease (Selkoe 2011), Parkinson's disease (Shulman et al 2011), Huntington's disease (Finkbeiner 2011), the frontotemporal dementias (Ferrari et al 2011;Seelaar et al 2011), and ALS (Ferrari et al 2011). In each of these disorders, there is a selective vulnerability of distinct neuronal populations to the neurodegenerative process, and the clinical manifestations of each disorder reXect the distinctive subpopulations of neurons involved.…”
Section: Applications To Age-related Human Inherited Neurodegenerativmentioning
confidence: 99%
“…Among the most common are age-related neurodegenerative disorders, such as Alzheimer's disease (Selkoe 2011), Parkinson's disease (Shulman et al 2011), Huntington's disease (Finkbeiner 2011), the frontotemporal dementias (Ferrari et al 2011;Seelaar et al 2011), and ALS (Ferrari et al 2011). In each of these disorders, there is a selective vulnerability of distinct neuronal populations to the neurodegenerative process, and the clinical manifestations of each disorder reXect the distinctive subpopulations of neurons involved.…”
Section: Applications To Age-related Human Inherited Neurodegenerativmentioning
confidence: 99%
“…In PD and related disorders such as PD dementia, dementia with Lewy bodies (DLB), and multiple system atrophy (MSA), the protein α-synuclein (α-syn) accumulates in neuronal and non-neuronal cells in cortical and subcortical nuclei as Lewy bodies, neuronal cytoplasmic inclusions, or glial cytoplasmic inclusions [4,5]. Furthermore, in FTD (amyotrophic lateral sclerosis spectrum disorder) aggregates of either tau, superoxide dismutase 1, TAR DNA-binding protein , or fused in sarcoma are found [6,7]. In addition, recent studies have shown that α-syn can accumulate in selected brain regions in AD [8], and that TDP-43 aggregates are found in the limbic system in AD and DLB [9].…”
Section: Introductionmentioning
confidence: 99%
“…The discriminant function was significant (Wilk's λ [7] = 0.372, p < 0.001), and all measures were included in the canonical function with loadings >0.40 (table 3). The canonical variable (raw score) was estimated using the following equation:…”
Section: Resultsmentioning
confidence: 99%
“…The clinical picture of ALS-FTD may be depicted as a tale of two illnesses [7]: a motor neuron disease paired with progressive cognitive impairment. The suggested continuum (leading from ALS to FTD) [8] is supposed to follow a course between two extremes over time, beginning with mild cognitive impairment and finally progressing to FTD (with the latter being a prognostic factor for poor survival) [9,10,11].…”
Section: Introductionmentioning
confidence: 99%